NOTCH3 Variants and Genotype-Phenotype Features in Chinese CADASIL Patients - Hu, Yacen; Sun, Qiying; Zhou, Yafang; Yi, Fang; Tang, Haiyun; Yao, Lingyan; Tian, Yun; Xie, Nina; Luo, Mengchuan; Wang, Zhiqin; Liao, Xinxin; Xu, Hongwei; et al. (Frontiers in Genetics, 2021)
Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a cerebral small vessel disease caused by mutations in the NOTCH3 gene. Archetypal disease-causing mutations are cysteine-affectting variants within the 34 epidermal growth factor-like repeats (EGFr) region of the Notch3 extracellular subunit. Cysteine-sparing variants and variants outside the EGFr coding region associated with CADASIL phenotype have been reported. However, the linkage between untypical variants and CADASIL is unclear. In this study, we investigated the spectrum of NOTCH3 variants in a cohort of 38 probands from unrelated families diagnosed as CADASIL. All coding exons of the NOTCH3 gene were analyzed and clinical data were retrospectively studied. We identified 23 different NOTCH3 variants including 14 cysteine-affecting pathogenic variants, 5 cysteine-sparing pathogenic variants, 2 reported cysteine-sparing variants of unknown significance (VUS) and 2 novel VUS outside EGFr region. In retrospective studies of clinical data, we found that patients carrying cysteine-sparing pathogenic variants showed later symptom onset than patients carrying pathogenic cysteine-affecting variants (51.36±7.06 vs. 44.96±8.82, P = 0.023) and milder temporal lobe involvement (1.50±1.74 vs. 3.11±2.32, P = 0.027) than patients carrying cysteine-affecting pathogenic variants. Our findings suggested that untypical variants comprise a significant part of NOTCH3 variants and may be associated with a distinctive phenotype.